Elias B.Lopez Hall room assignment system using genetic algorithm - Pelenio, Kiara Rna G. (2011)
Optimization is the process of making the best or most effective use of a situation, opportunity, or resource. Genetic algorithm is one of the numerous methods developed for optimization. It is a popular method for avoiding local optima in improving search. Genetic algorithm has been categorized as an effective algorithm in addressing certain range of scheduling problems. One of the instances wherein genetic algorithm can be applied is in the room assignment of the University of the Philippines Mindanao dormitory, the Elias B. Lopez Hall (EBL Hall). At present, direct heuristics is still the utilized method in arranging student residents in the dormitory. Assigning rooms to each student is not at all an easy task since several factors are needed to be considered. Factors include at most four students of the same sex can be assigned per room, students from the same/close provinces or cities are encouraged to be grouped during hte first semester, students from the same /related courses are also encouraged to be grouped together during the second semester, at least 1 upperclassman must be assigned in each room, and the least number of rooms must be occupied for energy-saving and maintenance purposes. Through this study, the EBL Hall Room Assignment System was created. This system automatically computes the student room assignment on the EBL Hall context using genetic algorithm. With this system , room assignment can be processed in a computerized manner in just a matter of minutes. The system also has a user friendly interface to help user in doing the room assignment process in an easy way.